Implementasi algoritma Floyd-Warshall untuk menentukan rute terpendek destinasi wisata populer di Labuan Bajo - Krisnamurti, Cyrenia Novella; Geong, Efrem Alfandro Pascal (Unnes Journal of Mathematics, 2021)
This study aims to (1) find a solution to the application of the Floyd-Warshall algorithm in determining the shortest route from Labuan Bajo Airport to 5 popular tourist destinations in Labuan Bajo and (2) determine the shortest recommended route in visiting 5 popular tourist destinations in Labuan Bajo if Labuan Bajo Airport is used as the initial position of the trip. The type of research used in this study is applied research. The object in this study is the route that connects Labuan Bajo Airport and 5 popular tourist destinations in Labuan Bajo. This study shows the progress of the Floyf-Warshall algorithm in determining the shortest route that connects the Labuan Bajo airport and 5 popular tourist destinations in Labuan Bajo with the recommended shortest route, namely: Labuan Bajo Airport → Pede Beach → Batu Cermin Cave → Bukit Cinta → Binongko Beach → Waecicu Beach with a path length of 15.28 kilometers